Implementation of the Host to Host System for Payment of Port Services at the BP Batam Office at PT. Snepac Shipping Batam - Naomi Novita Purba; Dirhamsyah Dirhamsyah; Masringgit Marwiyah Nst (Jurnal Riset dan Inovasi Manajemen, 2024)
Snepac Shipping Batam is a shipping company engaged in the field of agency services. In the sense of a representative of (Shipping agency) for the management of ship documents and the management of ship needs at the destination port. In compiling this paper the author uses several methodologies during the land practice, namely the field method (field research) and the library method (library research). To find out and get closer to how the shipping company PT. Snepac Shipping Batam carries out ship service activities according to ship needs at the port. This paper aims to find out the implementation of the host to host system for port service payments at the BP Batam office. BP Batam is the Batam Sea Management Agency where BP Laut Batam is an agency that plays an important role in handling ships entering the Batam port area which provides a port as a place for ships to carry out activities both in the loading and unloading process or ship guidance and towing activities. Under the supervision of BP Laut Batam, this agency has an important role in regulating everything related to the port, starting from regulating port costs which include mooring, guiding and towing costs needed by the ship.